2011
DOI: 10.1016/j.puhe.2011.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of the female condom in a male condom-only intervention in the sex industry in China: A cross-sectional analysis of pre- and post-intervention surveys in three study sites

Abstract: SUMMARYObjectives-To describe female condom (FC) use, male condom (MC) use and overall levels of protected sex before, during and after FC education and promotion (using the original prototype FC) combined with MC promotion among female sex workers in three rural or small urban settings in southern China.Study design-The 1-year FC intervention was conducted by local health workers through outreach to establishments where sex work is conducted. Three serial cross-sectional surveys were conducted in each study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 24 publications
1
24
1
Order By: Relevance
“…Of particular note was the interest in the device by women working in the entertainment industry, both because of the ability of the device to provide dual protection and because it was female-initiated. This interest in, and willingness to use, the Woman's Condom by women working in the entertainment industry is consistent with reports of their interest and use of other female condom products 2224…”
Section: Discussionsupporting
confidence: 84%
“…Of particular note was the interest in the device by women working in the entertainment industry, both because of the ability of the device to provide dual protection and because it was female-initiated. This interest in, and willingness to use, the Woman's Condom by women working in the entertainment industry is consistent with reports of their interest and use of other female condom products 2224…”
Section: Discussionsupporting
confidence: 84%
“…The female condom (FC), a woman-initiated novel barrier method that is as effective as male condoms (MC) for both STI and pregnancy prevention (Kaler, 2004; Liao, Weeks, Wang, Nie, et al, 2011; Mantell et al, 2006; Weeks, Hilario, et al, 2010) is largely under-promoted for prevention worldwide. The different and awkward appearance of the FC and the typical initial difficulty of insertion (Choi, Gregorich, Anderson, Grinstead, & Gomez, 2003; Smit, Beksinska, Vijayakumar, & Mabude, 2006; Vijayakumar, Mabude, Smit, Beksinska, & Lurie, 2006) often lead potential new users to reject FC before trying it or after the first use, and induce health care providers and educators to dismiss it before giving sufficient effort to get potential users past the initial barriers (Mantell et al, 2011).…”
Section: Multilevel Intervention To Reduce Hiv/sti Risk Among Chinesementioning
confidence: 99%
“…A multi-level ecological model, focused primarily on linear associations among factors in the contexts inside sex-work establishments, guided our intervention design and methodological approach. Analyses based on that approach, presented elsewhere (Liao, Weeks, Wang, Nie, et al, 2011; Liao, Weeks, Wang, Li, et al, 2011; Nie et al, in press; Weeks, Liao, et al, 2010), indicated some successes in reducing sexual risk in the target population of women working in sex-work establishments in the four study towns, and also demonstrated important differences across study sites in intervention processes and outcomes.…”
Section: Introductionmentioning
confidence: 98%
“…Since FC was first introduced, studies of acceptability and usage have been widely conducted among sex workers (Witte, El-Bassel, Wada, Gray, & Wallace, 1999; Jivasak-Apimas et al, 2001; Cheng et al, 2002; Zachariah, Harries, Buhendwa, Spielman, Chantulo, & Bakali, 2003; Thomsen et al, 2006; Hoke et al, 2007; Lara, Grossman, Munoz, Rosario, Gomez, & Garcia, 2009; Mack, Grey, Amsterdam, Matta, & Williamson, 2010; Liao et al, 2011a; Liao et al, 2011b), couples (Musaba, Morrison, Sunkutu, & Wong, 1998; Lawson et al, 2003; Smita et al, 2005; Lameiras Fernandez, Failde Garrido, Castro, Nunez Mangana, Carrera Fernandez, & Foltz, 2008), patients from clinics (Artz et al, 2000; Hoffman, Exner, Leu, Ehrhardt, & Stein, 2003; Kulczycki, Kim, Duerr, Jamieson, & Macaluso, 2004), and volunteers (Barbosa, Kalckmann, Berquo, & Stein, 2007). Despite numerous studies demonstrating high acceptability of FC among various populations, its use remains low and a large proportion of women who initially tried it did not sustain its use (Hoffman et al, 2004; Gallo, Kilbourne-Brook, & Coffey, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, about 94% of women in the intervention reported liking FC, and 97% expressed that they would use it in the future (Cheng et al, 2002; Cheng et al, 2003). Liao et al reported findings from cross-sectional surveys in three study sites in southern China conducted by our project team, in which about 25%–50% of the study participants reported using FC; of these, only 10%–30% used it more than once after FC intervention, but this varied by study site (Liao et al, 2011b). All of these studies indicated that, although FC provides dual protection from STI and unwanted pregnancy, it might not be considered an alternative option for all FSW in China.…”
Section: Introductionmentioning
confidence: 99%